2003
DOI: 10.4018/jgim.2003070102
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on IS Risks and Failure Types

Abstract: Information systems (IS) designers from the United States, Japan, and Korea were surveyed to explore potential similarities and differences in their views on two IS risk factors, various types of IS failure and the overall failure rate on IS projects. While there were only a few differences between the U.S. and Japan, there were a number of differences in the views of designers from the U.S. and Korea. The results revealed that a lack of user involvement and a lack of experienced IS personnel were perceived as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is useful for MIS practitioners, dealing with multiple subsidiaries of a multinational firm or for MIS vendors engaged with clients and their facilities across the globe, to understand differences among IS managers. As an example, a number of studies (Choi & Choi, 2003;Peterson & Kim, 2003) indicated that in different countries managers of MIS projects perceive projects and project risk differently. Additionally, IS managers in different localities prioritized key issues differently (Alshawaf & DeLone, 2002) and shape policy toward IT governance differently (Chin et al, 2004).…”
Section: Managerial Behavior/ Attitudes and Workforcementioning
confidence: 99%
“…It is useful for MIS practitioners, dealing with multiple subsidiaries of a multinational firm or for MIS vendors engaged with clients and their facilities across the globe, to understand differences among IS managers. As an example, a number of studies (Choi & Choi, 2003;Peterson & Kim, 2003) indicated that in different countries managers of MIS projects perceive projects and project risk differently. Additionally, IS managers in different localities prioritized key issues differently (Alshawaf & DeLone, 2002) and shape policy toward IT governance differently (Chin et al, 2004).…”
Section: Managerial Behavior/ Attitudes and Workforcementioning
confidence: 99%
“…Korea is deemed to be more risk averse than the US An evaluation of software risks by Peterson and Kim (2003) found there were few differences between the US and Japan, yet a number of differences were found between the US and Korea. Specifically, a lack of experienced IS development personnel was perceived to be a greater risk factor in Korea than in the US This difference adds some weight to Hofstede's five cultural differences studies among more than 50 countries (ITIM International, 2006).…”
Section: Relevant Literaturementioning
confidence: 99%